(untitled) (Communications in Mathematical Research, 2025)
Let R be an associative ring with identity. In this paper, we consider generalizations of Gorenstein FP-injective R-modules and FP-injective complexes, give the definitions and characterizations of strongly Gorenstein FP-injective R-modules and strongly FP-injective complexes, which are induced by strongly FP-injective modules. Then we investigate the strongly FP-injective dimension of complexes.